Implementation of Recollection in Preschool Learning Based on Plato's Philosophy Perspective - Enjang, Enjang; Kusnandar, Enan; Nurhayati, Tati (International Conference on Islamic Studies, 2024)
This research attempts to describe the extent of the influence of using Plato's recollection/anamnesis model in the learning process so as to produce students who have high memory and are able to understand eidos (the realm of ideas/knowledge) well. The method used is descriptive qualitative with a phenomenological approach which describes the implementation of Plato's recollection model in the learning process. Data from this research were obtained through interviews with the principal and educators at RA/KB Al-FathurRochman who were the main sources of this research, then interviews with students (early childhood at the school) and also the parents of the students concerned, observations in the form of passive participant observation and documentation as supporting data from the interview results. The percentage of children who understand eidos reaches 80.95% of 40 students, where children experience improved memory and are more creative and productive, and the remaining 19.05% of students, even if they can adapt to the recollection model, still have not experienced the improvement as expected. The research results prove that every student can utilize noesis in the thinking or reasoning process so that they are able to remember every learning process that has been carried out which in the end is able to produce reliable students, especially in achieving eidos (the realm of ideas/knowledge).